PECULIARITIES IN THE MANIFESTATION OF THE LOWER LIMBS’ EXPLOSIVE POWER IN CHILDREN OF PRESCHOOL AGE - D. Simeonova; K. Naidenova (Trakia Journal of Sciences)
Physical Education is a vital aspect of the preschool curriculum in the education system. Its main tasks are aimed at a child's comprehensive development. It influences health, physical fitness, and communication skills, helps cognitive growth, and provides emotional satisfaction from motor activity. One of the key activities in the subject's curriculum is the development of children's motor skills. The work on explosive power is essential here, as it directly influences the mastery and subsequent improvement of natural movements.Based on the above, this study aimsto reveal the peculiarities in the manifestation of the lower limbs’ explosive power in children of preschool age. To realize the aim, we carried out a one-time test with 251 children (boys and girls) from two kindergartens in the territory of the city of Sofia. Each child's participation was confirmed by signing an informed consent form by their parents. Methods: We conducted the research by applying the followingtests: standing long jump with two legs and consecutive single-leg hops.Results: We subjected the test data to variation and comparative analysis. The variation analysis results showed a normal distribution of the subjects' average achievements, which allowed us to apply a two-factor analysis of variance followed by the parametric Student's t-test. The data from the two-factor ANOVA showed significant effects of the factors of gender and age. The comparisons between different ages allow us to follow the dynamics of the development of the lower limbs’ explosive power. Conclusion: After conducting research and processing the results, we found significant age and gender differences in preschool children's abilities regarding the lower limbs’ explosive power. This allows us to recommend work on developing lower limbs’ explosive power based on the inferred intergroup differences.